2015
DOI: 10.1007/s13346-015-0222-6
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer efficacy and toxicokinetics of a novel paclitaxel-clofazimine nanoparticulate co-formulation

Abstract: Contemporary chemotherapy is limited by disseminated, resistant cancer. Targeting, nanoparticulate drug delivery systems that encapsulate synergistic drug combinations are a rational means to increase the therapeutic index of chemotherapeutics. A lipopolymeric micelle co-encapsulating an in vitro optimized, synergistic fixed-ratio combination of paclitaxel (PTX) and clofazimine (B663) has been developed called Riminocelles™. The present pre-clinical study investigated the acute toxicity, systemic exposure, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition, clofazimine has been shown to exert an inhibitory action on ABCB1/MDR1/P-glycoproteins (Pgp) [58], although this aspect is particularly relevant when applied together with chemotherapeutics to chemo-resistant cells (e.g. [59]). Finally, clofazimine has been shown via bioinformatic screening to have the potential to inhibit p53–MDM2 interaction leading in turn to stabilization and activation of the tumor suppressor p53 [60, 61].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clofazimine has been shown to exert an inhibitory action on ABCB1/MDR1/P-glycoproteins (Pgp) [58], although this aspect is particularly relevant when applied together with chemotherapeutics to chemo-resistant cells (e.g. [59]). Finally, clofazimine has been shown via bioinformatic screening to have the potential to inhibit p53–MDM2 interaction leading in turn to stabilization and activation of the tumor suppressor p53 [60, 61].…”
Section: Discussionmentioning
confidence: 99%
“…Koot et al showed that Riminocelles™, a formulation of co-encapsulated paclitaxel and clofazimine, demonstrated superior efficacy in preclinical studies. 7 Batist et al demonstrated for the first time, that CPX-1, a liposome formulation co-encapsulated with irinotecan and floxuridine, was well tolerated and exhibited antitumor activity in patients with advanced solid tumors in a Phase 1 study. 8 Therefore, administering various chemotherapeutic drugs together as appropriate nanocarrier formulations may be a promising strategy for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These differences highly complicate and make unlikely that the free drug combinations reach the target site at optimal ratios guaranteeing synergistic effects. However, the use of multifunctional nanocarriers that accommodate in their structure more than one drug at a fixed ratio appears a unique opportunity to overcome this problem. …”
Section: Introductionmentioning
confidence: 99%